A Comprehensive Definition of the Concept of Innovation in Russian and International Science - Manuylenko, Vikroriya Valeryevna; Mishchenko, Andrey Aleksandrovich; Bigday, Olga Borisovna; Putrenok, Yekaterina Leonidovna; Savtsova, Anna Valeryevna (International Journal of Economics and Financial Issues, 2015)
Theoretical and methodological studies of innovation content and essence show that methodological assessment approaches fail to represent an explicit conceptual and categorical framework for the category under consideration, which carries ambiguous connotations both in Russian and foreign theory of innovation. This paper explores the essential theoretical conceptual properties of innovation, which is considered a system enabling to argue that a system-wide definition of the innovation concept is the most preferable in terms of comprehensiveness. From a theoretical perspective, we have provided insight into the innovative process by stages within the innovation system, and presented a set of innovation functions, including intensive development and reputation functions; we have traced the logical interrelation between such concepts as 'idea', 'novelty', 'invention', 'innovation', 'innovative product', 'innovative service', 'innovative product line'. It is assumed that a methodological innovation assessment should be based on a comprehensive synergy-oriented approach. The methodological principles for the innovation system construction have been formed. Keywords: innovations; innovative process; innovation functions JEL Classifications: B4; D2; L1